2014
DOI: 10.1002/stem.1759
|View full text |Cite
|
Sign up to set email alerts
|

The Regulatory Landscape of Osteogenic Differentiation

Abstract: Differentiation of osteoblasts from mesenchymal stem cells (MSCs) is an integral part of bone development and homeostasis, and may when improperly regulated cause disease such as bone cancer or osteoporosis. Using unbiased high-throughput methods we here characterize the landscape of global changes in gene expression, histone modifications, and DNA methylation upon differentiation of human MSCs to the osteogenic lineage. Furthermore, we provide a first genome-wide characterization of DNA binding sites of the b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
90
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(98 citation statements)
references
References 72 publications
8
90
0
Order By: Relevance
“…5B, we found that these histone marks followed the expected genomic distribution profiles when all gene bodies throughout the genome are averaged together to display the ChIP-seq tag densities as reported previously (54). During differentiation, peaks shifted in amplitude (greater or lesser peak reads) but not necessarily in location, similar to recent observations (55). This was demonstrated in Fig.…”
Section: Msc Differentiation Is Driven By Specific and Unique Transcrsupporting
confidence: 87%
“…5B, we found that these histone marks followed the expected genomic distribution profiles when all gene bodies throughout the genome are averaged together to display the ChIP-seq tag densities as reported previously (54). During differentiation, peaks shifted in amplitude (greater or lesser peak reads) but not necessarily in location, similar to recent observations (55). This was demonstrated in Fig.…”
Section: Msc Differentiation Is Driven By Specific and Unique Transcrsupporting
confidence: 87%
“…We used ChIP-seq experiments generated in Gm12878, HelaS3, H1hesc, K562, and MCF7 cell lines. ChIP-seq data for Runx1 and Runx2 were retrieved from the NCBI Gene Expression Omnibus database (Edgar et al, 2002), with accession number GSE45144 for Runx1 in human hematopoietic stem and progenitor cells (HSPCs) (Beck et al, 2013), and GSE49585 for Runx2 in cultured human osteoblasts (Hakelien et al, 2014). …”
Section: Methodsmentioning
confidence: 99%
“…The iMSC#3 GM group consisted of the experiment accession ERX302478 (run accession ERR329500) and ERX302479 (run accession ERR329502) while the iMSC#3 DM group contained theexperiment accession ERX302480 (run accession ERR329501) and ERX302481 (run accession ERR329499). RNA libraries were sequenced with the Illumina Genome Analyzer II system according to the manufacturer protocols (FC-104-5001; Illumina, San Diego, CA, USA), by performing a paired-end run with 75 bp read length for all samples (Hakelien et al, 2014) .…”
Section: Datasetsmentioning
confidence: 99%